Investigation of hearing loss in patients with acute brucellosis by standard and high-frequency audiometry - Kaygusuz, TO; Kaygusuz, I; Kilic, SS; Yalcin, S; Felek, S (Elsevier Sci Ltd, 2005)
This study aimed to determine the effect of acute brucellosis on the auditory system. Forty-two patients with acute brucellosis were evaluated clinically, and with serological and audiological tests, before and after treatment. Hearing threshold averages were calculated at 11 different frequencies (250-8000 Hz) of the auditory airway, and statistical analysis was performed. The average hearing thresholds were > 20 dB, with standard audiometry at 6000-8000 Hz, and < 20 dB at all other frequencies. After treatment, the average auditory threshold decreased to < 20 dB at 6000-8000 Hz (p < 0.0001). Pure-tone hearing thresholds were improved at all frequencies after treatment, with statistically significant differences at all frequencies except 12 000, 14 000 and 16 000 Hz (p < 0.05). There was no permanent hearing loss caused by acute brucellosis, and hearing thresholds were restored after treatment. It was concluded that acute brucellosis affects the auditory system, especially at high frequencies, and that patients with all forms of brucellosis should be evaluated for hearing loss.
Keywords: audiometry; auditory system; brucellosis; hearing loss; high-frequency audiometry; standard-frequency audiometry